Quetiapine Attenuates Schizophrenia-Like Behaviors and Demyelination in a MK-801–Induced Mouse Model of Schizophrenia - He, Jue; Zu, Qian; Wen, Chunyan; Liu, Qianqian; You, Pan; Li, Xinmin; Wang, Wenqiang (Frontiers in Psychiatry, 2020)
Brain demyelination is possibly one of the main pathological factors involved in schizophrenia, and targeting on myelination may be a useful strategy for schizophrenia treatment. Quetiapine, a widely used atypical antipsychotic drug for schizophrenia treatment, has been reported to have neuroprotective effects on cerebral myelination in a demyelination animal model. The objective of the present study was to evaluate the effect and underlying neuroprotective mechanism of quetiapine on the schizophrenia-like behaviors and possible cerebral demyelination induced by MK-801, an N-methyl-D-aspartate glutamate receptor antagonist. Mice were treated with chronic quetiapine (10 mg/kg/day, intraperitoneally) for 28 days. From day 22 to 28, 1 h after the administration of quetiapine, the mice were administered MK-801 (2 mg/kg/day, subcutaneously). The positive symptom of schizophrenia was measured in a locomotor activity test on day 29, the memory was evaluated by a Y-maze test on day 30, and the sensorimotor gating deficit in mice was measured by prepulse inhibition test on day 31. After the behavioral tests, the protein expression of myelin basic protein (MBP) was measured by Western Blot, and the protein expression of brain-derived neurotrophic factor (BDNF) was measured by ELISA in the frontal cortex of mice. Our results showed quetiapine attenuated schizophrenia-like behaviors including hyperactivity, memory impairment, and sensorimotor gating deficit in the MK-801 mice. In the same time, quetiapine attenuated demyelination, concurrent with attenuated BDNF decrease in the brain of MK-801-injected mice. These results suggest that the beneficial effects of quetiapine on schizophrenia might be partly related to its neuroprotective effect on brain myelin basic protein and its upregulating neuroprotective proteins such as BDNF, and indicate that modulation of cerebral demyelination could be a novel treatment target of schizophrenia.